2020
DOI: 10.1186/s12974-020-01830-4
|View full text |Cite
|
Sign up to set email alerts
|

Stimulator of IFN genes mediates neuroinflammatory injury by suppressing AMPK signal in experimental subarachnoid hemorrhage

Abstract: Background: Neuroinflammation is closely associated with the poor prognosis in subarachnoid hemorrhage (SAH) patients. This study was aimed to determine the role of stimulator of IFN genes (STING), an essential regulator to innate immunity, in the context of SAH. Methods: A total of 344 male C57BL/6 J mice were subjected to endovascular perforation to develop a model of SAH. Selective STING antagonist C-176 and STING agonist CMA were administered at 30 min or 1 h post-modeling separately. To investigate the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(109 citation statements)
references
References 65 publications
3
106
0
Order By: Relevance
“…Recent studies indicated that activation of STING could promote microglial activation in several in ammatory models [53][54][55].The role of microglial activation in the development of SNI-induced neuropathic pain was corroborated by several pieces of evidence [30,56]. In our effort to clarify the mechanisms underlying microglia activation, we found that microglia and microglial response (including morphological change, proliferation, and release of mediators such as IL-1β, IL-6 and TNF-α) are essential for the induction of neuropathic pain after peripheral nerve injury [31].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicated that activation of STING could promote microglial activation in several in ammatory models [53][54][55].The role of microglial activation in the development of SNI-induced neuropathic pain was corroborated by several pieces of evidence [30,56]. In our effort to clarify the mechanisms underlying microglia activation, we found that microglia and microglial response (including morphological change, proliferation, and release of mediators such as IL-1β, IL-6 and TNF-α) are essential for the induction of neuropathic pain after peripheral nerve injury [31].…”
Section: Discussionmentioning
confidence: 99%
“…SAH is a form of stroke often resulting from a ruptured aneurism or CNS injury ( Tenny and Thorell, 2020 ). Recently, Peng et al (2020) found increased STING and p-TBK1 protein expression 12 h post-injury in a mouse model of SAH. The administration of a STING agonist, CMA in SAH mice worsened the neuronal damage and neurobehavioral deficits when compared to vehicle-treated mice.…”
Section: Sting Activity In Acute Cns Pathologiesmentioning
confidence: 99%
“…The administration of a STING agonist, CMA in SAH mice worsened the neuronal damage and neurobehavioral deficits when compared to vehicle-treated mice. In contrast, administration of a small-molecule STING inhibitor C-176 shortly after SAH modelling conferred neuroprotection by reducing brain oedema, neuronal damage and attenuated the upregulation of pro-inflammatory microglial markers including IL-1β, iNOS and caspase-1 ( Peng et al, 2020 ). Upregulation of STING signalling has also been reported in rats 48–72 h after neonatal HI ( Gamdzyk et al, 2020 ).…”
Section: Sting Activity In Acute Cns Pathologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A Western blot analysis was performed as previously described [23]. Brie y, the basal ganglia were homogenized and centrifuged for 15 min (13,000 g, 4 °C).…”
Section: Western Blot Analysismentioning
confidence: 99%